Investigation of Possible Causes of the Additional Torque on the Yacht’s Rudder - Soukup, Lubomír; Štigler, Jaroslav; Kharicha, Abdellah (EDP Sciences, 2016)
The present article deals with investigation of possible causes of the additional torque on the yacht’s rudder. One of the most important aspect for design of yachts are the symmetric conditions of all parts, which are located under water level and concentricity of the ship’s screw, rudder and keel relative to the hull. These symmetric and concentricity conditions have a major impact on the resulting dynamic properties of the ships. They have either substantial impact on the overall efficiency of installed engine and ship’s screw. As the result of poorly designed above mentioned parts, there can be an unsolicited additional torque on the yacht’s rudder and higher consumption of the fuel. Last but not least of these problems leads to poor controllability and discomfort within steering. This article is focused on the investigation of possible causes of the additional torque on the yacht’s rudder.

The present article deals with investigation of possible causes of the additional torque on the yacht’s rudder. One of the most important aspect for design of yachts are the symmetric conditions of all parts, which are located under water level and concentricity of the ship’s screw, rudder and keel relative to the hull. These symmetric and concentricity conditions have a major impact on the resulting dynamic properties of the ships. They have either substantial impact on the overall efficiency of installed engine and ship’s screw. As the result of poorly designed above mentioned parts, there can be an unsolicited additional torque on the yacht’s rudder and higher consumption of the fuel. Last but not least of these problems leads to poor controllability and discomfort within steering. This article is focused on the investigation of possible causes of the additional torque on the yacht’s rudder.
Investigation of Possible Causes of the Additional Torque on the Yacht’s Rudder
Keywords: Numerical Simulation; Yacht; Rudder; Torque; Numerical Simulation; Yacht; Rudder; Torque